(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Education with philosophy has a close relationship since philosophy is a perspective on life that prompts the goal of education. The perpetual view at the moment that education is viewed as a holder to coordinate the focal point of culture. While individuals can take care of the issue and achieve its objectives certainly. This state of progress in the movement of philosophy one of which is basic. Additionally, education as an apparatus to process acculturate human, with the refinement of introduction and philosophy that transformed into his conviction. In this paper we will talk about going to philosophical elements of education and the relation among philosophy and education.